Persistency with estrogen replacement therapy among hysterectomized women after the Women's Health Initiative study. (2nd November 2015) - Kyvernitakis, I.; Kostev, K.; Hars, O.; Albert, U-S.; Kalder, M.; Hadji, P.
ABSTRACT: Objectives Many women are reluctant to undergo estrogen replacement therapy (ERT) and discontinue the treatment within 12 months. The aim of this study was to investigate the persistence rates of ERT in hysterectomized women over the past decade, reflecting changes in the post-Women's Health Initiative (WHI) era. Methods We analyzed 8045 patients receiving ERT from 2004 to 2013 using the Disease Analyzer database. Results After 12 months of follow-up, only 24.6% of patients receiving 1 mg and 24.5% of patients receiving 2 mg of oral ERT were still on treatment ( p  < 0.0001). The persistency rate of patients receiving <50 μg of transdermal ERT was 28.6% compared to 33.5% for patients receiving >50 μg within the 12 months of follow-up. ERT that began in 2007–2009 was associated with a higher discontinuation rate (hazard ratio 1.06, p  = 0.0660) than ERT that began in 2010–2013 (hazard ratio 0.88, p  = 0.0001). Conclusions Our results indicate low persistency rates in women on ERT irrespective of the dose as well as the route of administration. However, a decrease in discontinuation rates was found when comparing women in the early vs. late post WHI era.